The Influence of Brand Experience through Customer Satisfaction and Brand Trust on Brand Loyalty in The Samsung Smartphone Brand - Tarigan, Zeplin Jiwa Husada; Yobeanto, Kelvin Leonardo (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
This research aims to analyze the influence of brand experience on satisfaction, loyalty, and brand trust among Samsung brand smartphone users. This research involved 163 respondents, consisting of current and former smartphone users. The results of the analysis show that brand experience has a positive influence on satisfaction, brand trust, and loyalty. The higher the user's perceived brand experience, the higher the level of satisfaction, trust, and loyalty to the Samsung brand. Satisfaction has also been proven to positively impact loyalty, where high satisfaction increases user loyalty to Samsung smartphones. In addition, brand trust plays an important role in building customer loyalty, where higher trust in a brand will increase the customer's tendency to remain loyal to using the product. The managerial implications of this research highlight the importance of building user communities on social media to increase customer engagement through sharing positive experiences regarding Samsung features. In addition, effective communication with customers must continue to be strengthened to provide education and resolve various obstacles faced by users, so as to strengthen trust and loyalty to the Samsung brand.